Shape Preserving Data Interpolation Using Rational Cubic Ball Functions - Ayser Nasir Hassan Tahat; Abd Rahni Mt Piah; Zainor Ridzuan Yahya (Journal of Applied Mathematics)
A smooth curve interpolation scheme for positive, monotone, and convex data is developed. This scheme uses rational cubic Ball representation with four shape parameters in its description. Conditions of two shape parameters are derived in such a way that they preserve the shape of the data, whereas the other two parameters remain free to enable the user to modify the shape of the curve. The degree of smoothness is C1. The outputs from a number of numerical experiments are presented.